2014
DOI: 10.1177/1479164114549553
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic therapies and cancer risk

Abstract: Aims: This review is aimed at highlighting the potential mitogenic/tumour growth-promoting or antimitogenic/tumour growth-inhibiting effects of the main antihyperglycaemic drug classes. Methods: We review and discuss the most current studies evaluating the association between antidiabetic medications used in clinical practice and malignancies as described so far. Results: Metformin seems to be the only antidiabetic drug to exert protective effects both on monotherapy and also when combined with other oral anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 218 publications
(238 reference statements)
1
26
0
6
Order By: Relevance
“…Metformin can improve treatment outcomes in preclinical models of cancer, particularly in the obese setting [1,3,58,86,112,118,127,152,164,170,178,181]. In addition, it reduces the incidence of cancer in diabetic patients as well as improves survival in newly diagnosed cases [28,94,97,102,144,152]. Metformin has been shown to target cancer cells, transcription factors, microRNAs, DNA damage, cancer stem cells, and metabolism [29,40,56,77,119,160].…”
Section: Potential New Links Between Obesity and Cancer: Obesity Is Amentioning
confidence: 99%
“…Metformin can improve treatment outcomes in preclinical models of cancer, particularly in the obese setting [1,3,58,86,112,118,127,152,164,170,178,181]. In addition, it reduces the incidence of cancer in diabetic patients as well as improves survival in newly diagnosed cases [28,94,97,102,144,152]. Metformin has been shown to target cancer cells, transcription factors, microRNAs, DNA damage, cancer stem cells, and metabolism [29,40,56,77,119,160].…”
Section: Potential New Links Between Obesity and Cancer: Obesity Is Amentioning
confidence: 99%
“…Furthermore, several glucose-lowering drugs have the potential to affect cancer risk [1]. For example, metformin therapy has been shown to decrease the risk of cancer, while other drugs may increase the risk of specific cancers [4]. Recently, concern was raised about a potential link between thiazolidinediones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a summarizing study, Lutz, et al (Lutz, et al, 2014) evaluated cancer risks of the major glucoselowering drug classes and confirmed the trends mentioned above. Favorable effects of metformin on several site-specific cancers were fairly significant, whereas insulin glargine had no effect.…”
Section: Dapagliflozinmentioning
confidence: 93%